Evolution of Agroforestry Research: A Bibliometric Study - Judijanto, Loso; Muhtadi, M.Ammar (West Science Agro, 2024)
This bibliometric study examines the evolution of agroforestry research over several decades, analyzing publication patterns, citation trends, and collaboration networks. Utilizing data from a comprehensive database, we identified major thematic areas including sustainability, carbon management, and the socioeconomic impacts on smallholder farmers. The analysis reveals a significant growth in the focus on environmental benefits such as carbon sequestration and biodiversity conservation within agroforestry systems. Additionally, the study highlights the key roles of influential researchers and outlines the dynamic collaboration networks that drive the field. By mapping the intellectual landscape of agroforestry research, this study provides both theoretical insights and practical implications, emphasizing the contribution of agroforestry to sustainable land management and climate change mitigation. This research not only charts past and current trends but also identifies under-researched areas, suggesting directions for future investigation.